THE UNITY GAIT OF TARBIYAH ISLAMIYAH IN ISLAMIC EDUCATION IN MINANGKABAU - Maimunah Maimunah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
In the early 20th century, Islamic scholars in Minangkabau are divided into two groups: the old and young groups. The old group is those in the field of faith committed themselves to the Ahlus Sunnah wal Jama'ah from Abu Hasan al-Asy’ari and Abu Muslim al-Maturidi. In the areas of worship, they are attached to Syafi’i. Although not all of them embrace the teachings of the congregation, in principle they admit the truth of mu’tabarah as defense from the young group. There are two main issues in that decision. The first is periama, the preservation issues of Sunniyah Syafi’iyah. The second is Minangkabau traditional preservation issues. These problems are summed up in one of the PERTI objectives, the results of the Bukititnggi congress which reinforce and strengthen adat nan kawi, syara' nan lazim in each country. The old group in Minangkabau strongly holds Syafi’i to be the foundation of every move in their struggle to both social and civic education.